Response of Chickpea (Cicer aritienum L.) to Sulphur and Zinc Nutrients Application and Rhizobium Inoculation in North Western Ethiopia - Beza Shewangizaw Woldearegay; Anteneh Argaw; Tesfaye Feyisa; Birhan Abdulkadir; Endalkachew Wold-Meskel (Turkish Journal of Agriculture: Food Science and Technology)
In sub-Saharan Africa, multiple plant nutrients deficiency besides nitrogen (N) and phosphorus (P) is a major growth-limiting factor for crop production. As a result, some soils become non-responsive for Rhizobium inoculation besides P application. Based on the soil test result, the soil of Experimental sites had low organic matter (OM), nitrogen (N), phosphorus (P), sulphur (S) and zinc (Zn)[xy1]. Hence, an experiment was carried out on-farm at Gondar Zuria woreda in Tsion and Denzaz Kebeles to evaluate the effect of Rhizobium inoculation, S and Zn application on yield, nodulation, N and P uptake of chickpea. The experiment included twelve treatments developed via factorial combination of two level of inoculation (Rhizobium inoculated, un-inoculated), three level of S (0, 15, 30 kg Sulphur ha-1) and two levels of Zn (0, 1.5 kg Zinc ha-1). The treatment was laid out in randomized complete block design with three replications. Results showed that the highest mean nodule number (15.3) and nodule volume (1.3 ml plant-1) over locations were obtained with Rhizobium inoculation integrated with 15 kg S and 1.5 kg Zn ha-1 which resulted in 37.8% and 116.7% increment over the control check, respectively. It was also observed that combined application of Rhizobium and 30 kg S ha-1 caused the highest (6.7) mean nodulation rating and seed yield (1775.5 kg ha-1) over locations which resulted in 86.1% and 28 % increase over the control check, respectively. Moreover, this treatment improved P use efficiency of chickpea. On the bases of observed result, it can be concluded that the response of chickpea to Rhizobium and P application can be improved by S application and Rhizobium inoculation with application of 30 kg S ha-1 with recommended rate of P and starter N is recommended for chickpea production at the experimental locations in Gonder Zuria Woreda.